2017
DOI: 10.1097/pgp.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

HPV-independent Differentiated Vulvar Intraepithelial Neoplasia (dVIN) is Associated With an Aggressive Clinical Course

Abstract: Differentiated vulvar intrapeithelial neoplasia (dVIN) is an human papillomavirus (HPV)-independent precursor of squamous cell carcinoma (SCC), and the aim of this study was to better characterize its natural history. Cases of dVIN were identified from the pathology archives. Outcomes of patients with dVIN only, without associated invasive SCC, were compared with a cohort of patients with high-grade squamous intraepithelial lesion [HSIL(VIN3)]. Eighteen patients diagnosed with dVIN with adjacent invasive SCC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 38 publications
2
63
0
2
Order By: Relevance
“…Additionally, some studies have shown that HPV-negative vulvar intraepithelial neoplasia (VIN) has a more aggressive clinical presentation with higher progression rate compared to HPV-positive VIN. 4,45,51,52 These findings could indicate that HPV-positive vulvar neoplasia in general develops through a less aggressive pathway and has a more favorable prognosis in all stages of carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, some studies have shown that HPV-negative vulvar intraepithelial neoplasia (VIN) has a more aggressive clinical presentation with higher progression rate compared to HPV-positive VIN. 4,45,51,52 These findings could indicate that HPV-positive vulvar neoplasia in general develops through a less aggressive pathway and has a more favorable prognosis in all stages of carcinogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…However, results from studies evaluating the radiosensitivity of HPV‐positive vulvar SCCs compared to HPV‐negative are conflicting and thus, we have not yet a full understanding of the molecular basis of a possibly higher radiosensitivity in HPV‐positive vulvar cancers. Additionally, some studies have shown that HPV‐negative vulvar intraepithelial neoplasia (VIN) has a more aggressive clinical presentation with higher progression rate compared to HPV‐positive VIN . These findings could indicate that HPV‐positive vulvar neoplasia in general develops through a less aggressive pathway and has a more favorable prognosis in all stages of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the presence of viral infection in HPV-associated cancers might confer an increased immune surveillance, which consequently makes the HPV-positive cancers less aggressive compared with those without viral epitopes (28). Studies have suggested that HPV-negative vulvar precancerous lesions have a more aggressive clinical presentation and higher progression rate compared with HPV-positive lesions (44,45), indicating that HPV-related precancerous lesions generally develop through a less aggressive pathway and have a more favorable prognosis in all stages of the carcinogenesis. Furthermore, for head and neck cancers it has been suggested that HPV-positive cancers could have a lower degree of gross genetic alterations or that the HPV status of the tumor might determine the molecular profile of the cancer, which could potentially influence the response to therapy (15,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, in contrast to the majority of VSCC being HPV‐negative, the majority of high‐grade VIN is HPV‐positive . Different factors might explain this paradoxical situation: (1) compared to HPV‐positive VIN, HPV‐negative VIN is both clinically and histopathologically less likely to be identified, and (2) HPV‐negative VIN appears to have a higher cancer progression risk of at least 30%‐35% with a shorter time interval between the precancerous VIN phase and invasive cancer . For HPV‐positive VIN, the cancer progression risk has been estimated between 3% and 9% in treated patients and about 16% in untreated patients …”
Section: Introductionmentioning
confidence: 99%